Determination of refractive index and thickness of a multilayer structure with a single terahertz time domain spectroscopy measurement - Sanjuan, Federico Ezequiel (2014)
A processing technique for the determination of the average refractive index and thickness of a two-layer system is presented. It is based on a single measurement with a standard terahertz time-domain spectrometer and the multilayer system thickness. The technique relies on the interference caused by the main pulse with the echoes produced in each material. This approach allows noninvasive inspection of double-layer compound products.